2004
DOI: 10.1038/oby.2004.82
|View full text |Cite
|
Sign up to set email alerts
|

A New Hand‐Held Indirect Calorimeter to Measure Postprandial Energy Expenditure

Abstract: ST-ONGE, MARIE-PIERRE, FREDERICK RUBIANO, ALFREDO JONES, JR., AND STEVEN B. HEYMSFIELD.A new hand-held indirect calorimeter to measure postprandial energy expenditure. Obes Res. 2004;12: 704 -709. Objective: To verify the accuracy of a new hand-held metabolic rate measuring device (MedGem) in quantifying postprandial energy expenditure (PP EE). MedGem measurements were compared to measurements obtained with a conventional indirect calorimeter (Delta-Trac). Research Methods and Procedures:The resting metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 13 publications
1
55
0
1
Order By: Relevance
“…Metabolic carts, such as the Deltatrac, have been shown to be reliable instruments for measuring RMR (Takala et al, 1989;Weissman et al, 1990;Tissot et al, 1995). Despite the advantages of the Deltatrac, there are factors that deter its use (Nieman et al, 2003;St-Onge et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic carts, such as the Deltatrac, have been shown to be reliable instruments for measuring RMR (Takala et al, 1989;Weissman et al, 1990;Tissot et al, 1995). Despite the advantages of the Deltatrac, there are factors that deter its use (Nieman et al, 2003;St-Onge et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional calorimeters have been described as costly and cumbersome, require skilled operators, possible off-site equipment repairs and calibration difficulties (Nieman et al, 2003;St-Onge et al, 2003). For these reasons, an inexpensive, easy-to-use, portable, and accurate device for measuring RMR in the clinical setting is desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current suggested set of equations (FAO, 2004) was derived from a revision of compiled data performed by Schofield (1985) from studies mainly conducted in the first half of the 20th century in samples that were not representative of any specific population. Initially in the tropics (geographic region of the Earth centered on the equator and limited by the Tropic of Cancer in the north and the Tropic of Capricorn in the South and characterized climatically by a dry and a wet season), and more recently in temperate regions (latitudes of the globe that lie between the tropics and the polar circles and characterized by four distinct seasons) (Henry and Rees, 1991;Alfonso-González et al, 2004;St-Onge et al, 2004), prediction equations have been shown to overestimate BMR (Wahrlich and Anjos, 2001a). The possible climatic influence on BMR was raised by Almeida (1919Almeida ( , 1920 who measured BMR in 20 Brazilians living in Rio de Janeiro (Tropics) and showed the values to be 20% lower than North-American men.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004 St-Onge and co-workers [11] evaluated the validity of the MG to measure the increase in energy expenditure associated with the consumption of a meal (postprandial energy expenditure; PP-EE). The study was set up to test RMR in 15 healthy adult subjects with a 20 minute measurement made using the DeltaTrac metabolic cart followed by 10 minute measurements using the MG. EE was measured for 7 hours following a meal which consisted of Ϸ600 kcal (2510 kJ) breakfast foods.…”
Section: Clinical and Field Studies Of Hand-held Indirect Calorimetersmentioning
confidence: 99%